Peningkatan Pengetahuan Ibu Tentang Gizi Seimbang Untuk Mencegah Permasalahan Gizi Pada Balita di Kabupaten Jember - Ria Chandra Kartika; Erna Selviyanti; Dessya Putri Ayu Umbaran; Dina Fitriyah; Yohan Yuanta (Indonesian Journal Publisher, 2022)
One of the characteristics of a developed nation is a nation that has a high level of health, intelligence and work productivity. These three things are strongly influenced by the state of nutrition. Nutritional problems in Indonesia are currently included in the triple burden of nutrition status. The prevalence of stunting under five in Indonesia is included in the chronic category, which is 30.8%. The direct cause of nutritional problems in toddlers is due to an unbalanced diet. Balanced nutrition is a food composition from a variety of food ingredients that contain nutrients needed by the body, both in quality and quantity. One of the efforts to prevent nutritional problems in toddlers is to empower parents of toddlers through increasing the knowledge of mothers of toddlers. The role of the mother is very important for toddlers to fulfill balanced nutrition because the level of knowledge about nutrition will affect the food selection process and family eating behavior. Therefore, this community service program is to carry out balanced nutrition counseling activities that aim to increase the knowledge of mothers of toddlers about balanced nutrition to prevent nutritional problems in toddlers. The target of this activity is mothers of children under five at Posyandu Catleya 19. The implementation of this activity was attended by mothers of children under five at Posyandu Catleya 19, posyandu cadres, and coordinating midwives. Counseling on balanced nutrition begins with pretest activities, then continues with material presentation, discussion and question and answer, and then closes with posttest. In this activity, mothers of children under five are given a balanced nutrition module which contains material on balanced nutrition and recipes that can be applied in daily feeding of children under five. The results of the activity evaluation showed that 76.3% of mothers under five experienced an increase in knowledge after counseling.